Pengembangan Modul Pembelajaran Berbasis WEB Pada Mata Kuliah PLC dan Pneumatic - Gusti Randa; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2020)
Based on the researcher's experience in taking PLC and Pneumatic courses in the fifth semester of 2018, the engineering faculty of the State University of Padang still uses manual books in printed form assisted by media in the form of power points where the media is less interactive and does not increase interest student self-study. Advances in information technology have enabled researchers to develop learning in changing the presentation of teaching materials, in this case, printed modules, into modules that are packaged in digital format, or known as electronic modules (e-modules). The research method used is R&D (Research & Development) and the model is 4D (Define, Design, Develop, and Disseminate). The research was conducted on students in the PLC and pneumatic courses at Padang State University. The questionnaire used in the study was a validation questionnaire and a student practicality questionnaire. In the distribution of validation questionnaires, the average results were obtained with a very valid category, on the distribution of practicality questionnaires to students, the scores were obtained in the practical category and some gave values ​​in the very practical category. With the average value obtained, the module media is said to be very practical. Based on the results of the research data, it is stated that the module is very valid and practical.